Developing a Water-Defendable and Dendrite-Free Lithium-Metal Anode Using a Simple and Promising GeCl4 Pretreatment Method - Liao, K.; Wu, S.; Mu, X.; Lu, Q.; Han, M.; He, P.; Shao, Zongping; Zhou, H. (Wiley - V C H Verlag GmbH & Co. KGaA, 2018)
© 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim Lithium metal is an ultimate anode in “next-generation” rechargeable batteries, such as Li–sulfur batteries and Li–air (Li–O2) batteries. However, uncontrollable dendritic Li growth and water attack have prevented its practical applications, especially for open-system Li–O2 batteries. Here, it is reported that the issues can be addressed via the facile process of immersing the Li metal in organic GeCl4–THF steam for several minutes before battery assembly. This creates a 1.5 µm thick protection layer composed of Ge, GeOx, Li2CO3, LiOH, LiCl, and Li2O on Li surface that allows stable cycling of Li electrodes both in Li-symmetrical cells and Li–O2 cells, especially in “moist” electrolytes (with 1000–10 000 ppm H2O) and humid O2 atmosphere (relative humidity (RH) of 45%). This work illustrates a simple and effective way for the unfettered development of Li-metal-based batteries.